Transformações no mercado de trabalho de Toledo - PR nos anos de 2002, 2010 e 2020: uma perspectiva à ocupação feminina - Girardi, Maira Perlin (2024)
The objective of this study is to analyze the formal labor market in the city of Toledo - PR, from a gender perspective, observing inequalities in labor income between women and men, related to education, age, sector and occupation, in the years 2002, 2010 and 2020. The aim is to identify the changes that have occurred with regard to gender and the extent of the disparities in female formal work income in relation to the variables mentioned above, in addition to verifying which public policies the municipality implements to combat inequalities of gender. To achieve these purposes, initially a literature review is addressed with the aim of delving deeper into the research topic and appropriate discussions. Then, the research uses secondary data collected from the Ministry of Labor and Employment (MTE - RAIS/CAGED) for the study period, in a qualitative and quantitative methodological format, and descriptive and exploratory research. In terms of investigating the existence of public policies and initiatives that aim to reduce inequalities, unstructured interviews were carried out with municipal public servants. The data obtained prove the increase in female participation in the formal labor market in Toledo – PR, and that wage disparities are more pronounced in the mineral extraction, public administration, services and commerce sectors, which results in a discriminatory formal labor market in the municipality. Public policies and initiatives were identified that seek to reduce the observed disparities, addressing actions such as combating violence against women, raising awareness and promoting female entrepreneurship. However, there is still much to be done both by the public authorities and by society in general.